From the implementation of environmental management accounting to organizational sustainability: Does stakeholder integration strengthen it? - Muhammad Amir; Zubir Azhar; Kishan A/L Krishnen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study investigates the impact of environmental management accounting implementation on organizational sustainability in the manufacturing sector of Pakistan, focusing on the moderating role of stakeholder integration (i.e., behavior of adaptation, interaction with stakeholders, and knowledge of stakeholders). This study employed a quantitative approach utilizing survey data from 267 ISO-certified manufacturing organizations. The study hypotheses were tested through partial least squares structural equation modeling by using SmartPLS software. Findings reveal that environmental management accounting implementation significantly improves organizational sustainability in economic, environmental, and social aspects. The relationship between environmental management accounting implementation and organizational sustainability is notably strengthened by stakeholder interaction and behavior of adaptation, which serve as significant moderators. In contrast, stakeholder knowledge alone indicates minimal impact on organizational sustainability. These results highlight the importance of incorporating stakeholder interaction and adaptability into environmental management accounting practices to maximize sustainability outcomes. This research contributes to theoretical knowledge by expanding stakeholder theory to encompass the dynamic role of stakeholder integration in environmental management accounting implementation for achieving sustainability. Practically, it offers empirical evidence for organizations and policymakers, stressing the need to promote adaptation and interaction with stakeholders through regulatory support and capacity-building programs.
Keywords: 330; Stakeholder theory; environmental management accounting; integration behavior; interaction with stakeholders; knowledge of stakeholders; organizational sustainability; ISO-certified firms